2014
DOI: 10.1016/j.jmb.2013.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Assembly of the Non-Covalent Spectrin Tetramerization Domain from Intrinsically Disordered Partners

Abstract: Interdomain interactions of spectrin are critical for maintenance of the erythrocyte cytoskeleton. In particular, "head-to-head" dimerization occurs when the intrinsically disordered C-terminal tail of β-spectrin binds the N-terminal tail of α-spectrin, folding to form the "spectrin tetramer domain". This non-covalent three-helix bundle domain is homologous in structure and sequence to previously studied spectrin domains. We find that this tetramer domain is surprisingly kinetically stable. Using a protein eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 62 publications
5
39
0
Order By: Relevance
“…The alanine mutant could then be used as an appropriate pseudo wild-type during analysis. These alanine-glycine (Ala-Gly) scanning mutations have been shown to specifically destabilize helical secondary structure (43,44) and have been used to probe helix formation in protein folding (45) and coupled folding and binding reactions (15,18,20). Eight positions along the solvent-exposed side of PUMA were subjected to Ala-Gly scanning (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alanine mutant could then be used as an appropriate pseudo wild-type during analysis. These alanine-glycine (Ala-Gly) scanning mutations have been shown to specifically destabilize helical secondary structure (43,44) and have been used to probe helix formation in protein folding (45) and coupled folding and binding reactions (15,18,20). Eight positions along the solvent-exposed side of PUMA were subjected to Ala-Gly scanning (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Biophysical techniques (12), NMR in particular (13), can characterize isolated IDPs in detail. Despite this progress, the number of studies examining kinetics and the mechanisms of binding remains relatively small (14)(15)(16)(17)(18)(19)(20)(21) given that the most commonly observed function of IDPs is in coupled folding and binding reactions (22).…”
mentioning
confidence: 99%
“…Interestingly it is seen that CD spectra reveals subtle differences in the folding and conformation of these spectrin domains which are consistent with previous literature on these domains. CD spectroscopy reveals that the lowest MRE values at 222 nm are those of the EF domain, SH3 domain and β‐tetramerization domain, which can be explained by the fact that β‐dimerization domain has a nonstructured tail (Hill, Kwa, Shammas, Lee, & Clarke, ) which decreases its α‐helical nature; similarly SH3 domain has a globular fold (Viguera et al, ) and EF domain while α‐helical is made up sequences nonhomologous to the spectrin repeat domain (Trave, Pastore, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hill et al found that this tetramerization domain is highly stable, and used protein engineering to describe the assembly mechanism of this domain. 24 The authors ultimately found that this mechanism is distinct from other known folding mechanisms of spectrin domains.…”
Section: Studies On Structural Properties Of Idps and Idprsmentioning
confidence: 95%